Motivating repeated readers in an Extensive Reading class: A critical reflection on course design - Nugrahenny T. Zacharias (Universitas Katolik Indonesia Atma Jaya, 2017)
Studies illustrating the effectiveness of ER in facilitating learners' development in reading fluency, speed and vocabulary have been reported in different contexts. However, studies exploring the extent to which ER accommodates repeated readers are almost absent from the literature. It is in this light that this paper proposes a number of motivating tasks that teachers may use to teach ER as a course. The present paper illustrates the task-based syllabus I developed for repeated readers. I will describe the series of motivating tasks and explain the rationale behind each